Structural diversity of Leiopathes glaberrima populations in the strait of Sicily: from pristine to declining forests - Giova, Antonio; Canese, Simonepietro; Donelli, Benedetta Zoe; Romeo, Teresa; Greco, Silvestro (Frontiers in Marine Science, 2024)
Introduction The black coral Leiopathes glaberrima is a key component of deep-sea animal forests of the Western Mediterranean and North-Atlantic hard bottoms. Due to its ecological role, biological characteristics and sensitivity to fishing activities, it has been included in the Annex II of the Barcelona Convention, listed as an endangered species in IUCN Red Lists, and recognized as an indicator of Vulnerable Marine Ecosystems by the FAO. Methods During a survey conducted in the Strait of Sicily, 140 ROV transects were carried out allowing the characterization of environmental preferences, associated fauna and population structure of L. glaberrima in the study area. Results and discussion 1020 colonies were distributed between 165 and 672 meters and arranged in 17 patches and isolated colonies. The average height was determined to be 40.9 ± 1.0 cm, with the range spanning from a minimum of 5 cm up to nearby 200 cm. Pristine colonies accounted for 62.9%, mainly constituted by small-sized individuals densely aggregated (up to 14.5/m2 in a single frame) in the eastern part of the area. 24.5% of the specimens were dead and localized in the western margin where we reported a rare case of mass mortality in the deep-sea environment and the first ever described for black corals, opening new scenarios regarding the possibility that these events can occur in environments previously considered safe from danger. The triggering causes of these events in inaccessible environments are actually only hypothesized, but it is not to be excluded that, sooner or later, a similar effect could potentially result from anthropogenic climate changes.